1998
DOI: 10.1136/bmj.317.7166.1111
|View full text |Cite|
|
Sign up to set email alerts
|

Factors affecting likelihood of applicants being offered a place in medical schools in the United Kingdom in 1996 and 1997: retrospective study   Commentary: League tables will help   Commentary: Some legal aspects arising from the study

Abstract: Objective To assess the relation between a range of measures and the likelihood of applicants to medical schools in the United Kingdom being offered a place overall and at each medical school, with particular emphasis on ethnic minority applicants. Design Data provided by the Universities and Colleges Admissions Service on 92 676 applications to medical schools from 18 943 candidates for admission in 1996 and 1997. Statistical analysis was by multiple logistic regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 17 publications
1
94
0
1
Order By: Relevance
“…Furthermore, multivariate analysis confi rms that the odds of being accepted for medicine are signifi cantly greater for those applicants from higher social classes. This analysis confi rms the fi ndings of past studies that demonstrate an important effect of social class in gaining entrance to medicine, 10,13 and that the social class effect in dentistry is not as marked as medicine. 9 Recent attempts to examine the low application rate for medicine by Greenhalgh et al suggest that socio-economic status can infl uence students' perceptions of medicine, 32 based on qualitative research fi ndings that suggest 'non-traditional' students, whose parents did not go to university, perceive medical school as 'distant, unreal, and culturally alien'.…”
Section: Socio-economic Statusmentioning
confidence: 54%
“…Furthermore, multivariate analysis confi rms that the odds of being accepted for medicine are signifi cantly greater for those applicants from higher social classes. This analysis confi rms the fi ndings of past studies that demonstrate an important effect of social class in gaining entrance to medicine, 10,13 and that the social class effect in dentistry is not as marked as medicine. 9 Recent attempts to examine the low application rate for medicine by Greenhalgh et al suggest that socio-economic status can infl uence students' perceptions of medicine, 32 based on qualitative research fi ndings that suggest 'non-traditional' students, whose parents did not go to university, perceive medical school as 'distant, unreal, and culturally alien'.…”
Section: Socio-economic Statusmentioning
confidence: 54%
“…[1][2] The debate with regard to ethnic and gender variation in applicants to HE has focused upon the disadvantages they may encounter in successfully gaining entry to their chosen course. McManus (1998), in a recent investigation of bias among applicants to medical schools, showed that even when academic achievement Fig. 1 Numbers of applicants to study medicine (left axis) and dentistry (right axis) for white and minority ethnic groups, 1994/5 to 1997.…”
Section: Methodsmentioning
confidence: 99%
“…3 He also noted that older applicants and those from lower socioeconomic groups are also disadvantaged. 3 These findings add to the ongoing debate on the selection process into medical schools.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 He also noted older applicants and those from lower socio-economic groups are also disadvantaged. These findings add to the ongoing debate on the selection process into medical and dental schools.…”
Section: Discussionmentioning
confidence: 99%